1997
DOI: 10.1152/ajpgi.1997.272.5.g1159
|View full text |Cite
|
Sign up to set email alerts
|

Correlation and comparison of magnetic and electric detection of small intestinal electrical activity

Abstract: superconducting quantum interference device magnetometer; basic electrical rhythm; spectral analysis; volume conductor; small intestine; electrical control activity; electrical recordings SMOOTH MUSCLE in the gastrointestinal tract displays two types of electrical activities. A high-frequency spiking activity known as the electrical response activity is associated with muscle contraction, whereas an oscillating slow wave, known as the electrical control activity or basic electrical rhythm (BER), is present con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
80
0
8

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(94 citation statements)
references
References 10 publications
5
80
0
8
Order By: Relevance
“…In a previous paper, we showed that the magnetic field from intestinal smooth muscle recorded outside the abdomen correlated highly with serosal electrode recordings. 15 We have also shown that the changes in small bowel electrical activity caused by intestinal ischaemia are reflected in SQUID recordings. 16 We showed that SQUID recordings were able to non-invasively detect the different frequencies of gastric magnetic fields (GMFs) at about 3 cpm and intestinal magnetic fields from 8 to 12 cpm, and that the locations of these frequencies was consistent with the known slow wave frequency profile of the gastrointestinal tract.…”
Section: Introductionmentioning
confidence: 77%
“…In a previous paper, we showed that the magnetic field from intestinal smooth muscle recorded outside the abdomen correlated highly with serosal electrode recordings. 15 We have also shown that the changes in small bowel electrical activity caused by intestinal ischaemia are reflected in SQUID recordings. 16 We showed that SQUID recordings were able to non-invasively detect the different frequencies of gastric magnetic fields (GMFs) at about 3 cpm and intestinal magnetic fields from 8 to 12 cpm, and that the locations of these frequencies was consistent with the known slow wave frequency profile of the gastrointestinal tract.…”
Section: Introductionmentioning
confidence: 77%
“…In 1997, Bradshaw et al showed that a high degree of correlation exists between the ECA frequency values determined using EGG and MGG (Bradshaw et al 1997). Whereas bioelectric fields depend on tissue permittivity and are therefore much attenuated by the multiple layers of electrical insulators of the abdominal walls and omentum, magnetic fields depend on the permeability of biological tissues, which is nearly equal to that of free space.…”
Section: Motivation and Purposementioning
confidence: 99%
“…However, this method entails several technical and intestinal signal coincides with the repetition rate of the internal intestinal SW both in physiological conditions [4] and in pathological conditions [8]. Nevertheless, the clinical application of surface EEnG recording still poses a series of difficulties: Surface-recorded myoelectrical signals are very weak [5,8], due to spatial filtering and the insulating effects of the abdominal layers [8]. In addition, external EEnG recording is contaminated by strong physiological interferences: cardiac activity, respiration, very lowfrequency components, and movement artifacts.…”
Section: Introductionmentioning
confidence: 99%
“…None of these methods can yet be used in clinical diagnosis, either because they require high-cost equipment, or because they are still in the experimental stage. The identifi cation of bowel slow wave (SW) activity at the abdominal surface has been accomplished by other authors [4,6,8]. In dogs, it has been proven that the dominant frequency of the external myoelectrical…”
mentioning
confidence: 99%